1964
DOI: 10.1126/science.144.3622.1137
|View full text |Cite
|
Sign up to set email alerts
|

Reduction of Dimethylsulfoxide to Dimethylsulfide in the Cat

Abstract: A peculiar sweetish odor was noted in the exhaled breath of cats treated with dimethylsulfoxide. By means of gas chromatographic and mass spectrographic techniques, the responsible compound was identified as dimethylsilfid.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

1965
1965
2013
2013

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 61 publications
(12 citation statements)
references
References 4 publications
0
12
0
Order By: Relevance
“…In man (Gerhards et al. 1965) and in animals (Distefano & Borgstedt, 1964;Throop, 1966), both dimethyl sulfone (DMS02) and DMS have been identified as metabolites. The inability to account (quantitatively) for the administered DMSO in animals suggests that its carbon structure is partially metabolized by mammalian systems (Kolb et al, 1966).…”
Section: Dmso As a Metabolite In Biological Systemsmentioning
confidence: 99%
“…In man (Gerhards et al. 1965) and in animals (Distefano & Borgstedt, 1964;Throop, 1966), both dimethyl sulfone (DMS02) and DMS have been identified as metabolites. The inability to account (quantitatively) for the administered DMSO in animals suggests that its carbon structure is partially metabolized by mammalian systems (Kolb et al, 1966).…”
Section: Dmso As a Metabolite In Biological Systemsmentioning
confidence: 99%
“…Certain pesticides are highly toxic to mammals when in the sulphoxide form, and microbial reduction may serve to detoxify them (Alexander, 1974). DMSO reduction to DMS has been shown in the cat (Distefano & Borgstedt, 1964), in the cow and other animals (Tiews et al, 1975) and in plants (Smale, Lasater & Hunter, 1975). Ando et al (1957) surveyed members of the Enterobacteriaceae and found that while all strains of Escherichia coli tested reduced DMSO, no strains of Shigella and only one out of 40 strains of Salmonella reduced it; they suggested that this reaction might be of diagnostic value.…”
Section: Introductionmentioning
confidence: 99%
“…Such small molecules undoubtedly would be lost during the food preparation and cooking procedures, and so those present in the urine must have arisen from a relatively stable precursor, unique to asparagus, that survives these processes and is eventually broken down during its journey through the human body. In addition, if they were initially presented to the mammalian metabolic systems, such small molecules would be rapidly and extensively degraded to inorganic sulfate and carbon dioxide with only trace amounts, if any, passing through the body unchanged to exit, probably, via the expired air (Canallakis and Tarver 1953;Distefano and Borgstedt 1964).…”
Section: Chemical Basis Of Urine Odormentioning
confidence: 99%